A System Dynamics Model of Land-use Change for Climate Change Adaptation: The Case of Uganda - Guma, Isdore Paterson; Semwanga Rwashana, Agnes; Oyo, Benedict (Scitepress science and technology publications, 2021)
System dynamics models in land use change are useful tools for understanding the cause and effect of land use changes, assessing the impacts of land use systems on the environment, and supports land use planning and policy dimensions. Several studies have used different methods to examine the drivers of land-use change in understanding the interactions of land-use change as a result of human activities. However, much less work has been undertaken to model the future of a suite of ecosystem services in a holistic way. These studies have been conducted with minimum emphasis on the systemic structures or feedback processes of land-use decisions. A system dynamics model will be used to model ecosystem services to understand complex interactions using dynamic synthesis methodology. Questionnaires and interviews will be used for data collection. The study will explore viable policies for optimal land use to mitigate the degree of future climate change and risks. Projections of future resource requirements and environmental stress are alarming as a result of poorly planned economic development. Unless significant measures are taken to incorporate environmental concerns, the situation is likely to worsen in the future. Modeling complex natural-human systems remains an important research area.
Keywords: System Dynamics Model; Land-Use Change; Climate; Climate Change Adaptation